Pengaruh Struktur Modal, Kebijakan Deviden, Ukuran Perusahaan dan Laba per Saham terhadap Nilai Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2014 2017 - Yuslinda Nasution (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2018)
The purpose of this study was to determine the effect of capital structure, dividend, firm size, and earnings per share simultaneously or partially on the value of companies in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The research approach used is a quantitative approach that serves to test the hypothesis proposed in the study and to answer the problems in this study. Samples taken were 32 manufacturing companies listed on the Indonesia Stock Exchange and active during 2014-2017. To get the information needed, the data collection process is carried out through documentation. For data collection methods carried out by collecting the company's annual financial statements. The research analysis tool used is multiple linear regression analysis. The results of the analysis show that the Capital Structure and Earnings Per Share have a partial effect on the Value of the Company. While simultaneously, this research variable has no effect on firm value.